IMPACT OF INVESTMENT, REGIONAL AND NATIONAL BUDGET CAPITAL EXPENDITURES ON MALUKU PROVINCE'S ECONOMIC GROWTH (2010-2022) USING MULTIPLE LINEAR REGRESSION - Tipka, Jefri; Matitaputty, Izaac Tonny (VARIANCE: Journal of Statistics and Its Applications, 2024)
Economic growth in Maluku Province is lower compared to several provinces in the Sulawesi Maluku Papua region. This research aims to analyze the influence of investment (foreign and domestic investment), regional and national budget capital expenditures (APBD capital expenditure and APBN capital expenditure) on economic growth in Maluku Province. This research uses secondary data from Maluku Province sourced from BPS for 2010-2022. The research method uses multiple linear regression with the SPSS application. The research results show that investment negatively and significantly affects economic growth. APBD capital expenditure and APBN capital expenditure have a positive and insignificant impact on economic growth in Maluku Province. This research implies that local governments must increase foreign and domestic investment and use capital expenditure effectively and efficiently to encourage economic development in Maluku.